船舶用スカイラジオメータの改良および南極観測船「しらせ」での初期観測結果 - 田中, 典章; タナカ, ノリアキ; 小林, 拓; コバヤシ, ヒロシ; 村山, 利幸; ムラヤマ, トシユキ; 塩原, 匡貴; シオバラ, マサタカ; Tanaka, Noriaki; Kobayashi, Hiroshi; Murayama, Toshiyuki; Shiobara, Masataka (2014)
P(論文) 動揺する船上においても太陽直達光を観測できるように，船舶用スカイラジオメータの太陽追尾性能を改良した．改良点は，太陽追尾精度の向上，測器視野角の拡大，太陽追尾速度の迅速化および測定手法の改良である．改良後の装置を用いて，第51次および第52次日本南極地域観測隊の本観測時に，南極観測船「しらせ」船上において太陽直達光および天空輝度分布を測定し，動揺した船上での直達光観測に成功した．直達光から算出された波長500nm における大気エアロゾルの光学的厚さは0.01-0.34であり，東南アジアおよび春季の西太平洋上で高い値を示した．オングストローム指数は－0.06～2.00の範囲であり，東南アジアおよびシドニー付近で最大を示した．今後，船舶用スカイラジオメータが，海洋上の大気エアロゾルに関する知見を深めると期待される． The sun-tracking performance of a shipborne sky radiometer was improved to attain accurate aerosol optical thickness (AOT) from direct solar measurements on a pitching and rolling vessel. Improvements were made in the accuracy of sun-pointing measurements, field-of-view expansion, sun-tracking speed, and measurement method. Radiometric measurements of direct solar and sky brightness distribution were performed using the shipborne sky radiometer onboard the Antarctic research vessel (R/V) Shirase during JARE-51 (2009-2010) and JARE-52 (2010-2011). The temporal variation of signal intensity measured by the radiometer under cloudless conditions was smooth, demonstrating that the radiometer could measure direct sunlight onboard the R/V. AOT at 500 nm ranged from 0.01 to 0.34, and values over Southeast Asia and over the western Pacific Ocean in spring were higher than those over other regions. The Angstrom exponent ranged from －0.06 to 2.00, and values over Southeast Asia and off the coast near Sydney were the highest. The improved shipborne sky radiometer will contribute to a good understanding of the nature of aerosols over the ocean. departmental bulletin paper